The role of social–emotional competencies in interpersonal relationships: a structural equation modeling approach - Lin, Jing; Zhang, Letong; Kuo, Yi-Lung (Frontiers in Psychology, 2024)
Social–emotional competencies, a crucial non-academic factor for K-12 students to be competent 21st century citizens, are receiving increasing research attention. Based on the 2,801 self-reports of grades 4–8 students from four schools in China, this study scrutinized the associations between adolescents’ five core competencies and their interpersonal relationships. Results indicated that five competencies acted as mediators between parent–child relationships and students’ relationships with teachers and peers. In addition to the girls’ advantage in five competencies, the results also demonstrated the gender and grade differences in the association. Boys had more indirect links and girls had both direct and indirect associations. There were grade differences in the mediating role of social awareness. The study’s findings may advance our understanding of the parental influence on Chinese students’ social–emotional competencies and provide a more nuanced picture of the conditions and interplay that foster or hinder students’ proficiency in these competencies in schools and families.